FEATURES OF THE ELECTRICAL CONDUCTIVITY AND RESISTANCE OF CEMENT FOR FIXATION OF NON-REMOVABLE PROSTHETIC - T.V. Perepelova; S.V. Mishchenko; T.A. Khmil; M.V. Khrebor; Yu.І. Sulenko; V.M. Sokolenko (Український стоматологічний альманах)
Our studies show different resistance and consequently different electrical conductivity of dry and wet samples of studied cements. Particular attention is drawn to the fact of reducing the relative value of the resistance of cements to fix after humidification. It can be evidence of higher hydrophobicity of the samples which have greater resistance after humidification. Thus, it is possible to recommend the use for fixing sintered structures made with reference bits according to our proposed method “Tsemion” and polycarboxylate cement. Since these cements have high electrical resistance and a corresponding lower electric conductivity, there is a slight decrease in the resistance after wetting the samples.